Defect and pyridinic nitrogen engineering of carbon-based metal-free nanomaterial toward oxygen reduction. (October 2018) - Zhang, Jian; Sun, Yuanmiao; Zhu, Jiawei; Kou, Zongkui; Hu, Pei; Liu, Lei; Li, Shuzhou; Mu, Shichun; Huang, Yunhui
Abstract: Defect and N-activated electronic engineering are of paramount importance for developing highly active carbon-based electrocatalysts toward oxygen reduction reaction (ORR) because the binding affinity of the carbon matrix can be efficiently tuned and thus promote the electrocatalytic activity. Herein, we present a facile and general strategy for fabricating pyridinic-N dominated and defect-enriched graphene-like nanocarbon material (ND-GLC) involving in-situ alkaline activation of cellulose and ammonia injection. The ND-GLC material has a superior and enhanced ORR activity and stability compared to commercial Pt/C catalyst in both rotating disk electrode measurements and Zn-air battery applications. Experimental and theoretical studies describe that the high electrocatalytic activity of ND-GLC mainly originates from the synergetic effect of edges/defects and pyridinic-N dopants. Importantly, our concept is demonstrated to be universal for other carbon-based nanomaterials (i.e., graphite nanoplates, carbon nanotubes, carbon nanospheres, graphene nanosheets). Graphical abstract: fx1 Highlights: Pyridinic-N and defect-enriched graphene-like carbon (ND-GLC) was fabricated. The ND-GLC catalyst shows an excellent ORR performance compared to Pt/C catalyst. DFT reveals that the defects and pyridinic-N can synergistically boost ORR activity. A general strategy for the development of high efficient carbon-based electrocatalysis.